“Exploring the Role of Leadership in Facilitating Change to Improve Digitalization in Portugal and Morocco: theoretical and empirical challenges” - Asensio, M.; Achouak Chalkha; Sousa, M. (EGPA Conference - Public Administration for the Sustainable Future of our Society, Lisbon, 6th-9th September 2022, 2022)
“The digital revolution in the context of North-South Cooperation: experiences from Morocco and Portugal” The Covid-19 pandemic has put Public Administration under enormous pressure and has offered opportunities to experiment with new practices for a more agile and resilient organization. This Panel sheds light on the digital solutions proposed in the context of North-South cooperation, looking at the experiences of Morocco and Portugal to guarantee access to public services, ensure continuity of education and support businesses facing difficult economic circumstances. These digital solutions encompass solutions in four areas: 1) skills; 2) infrastructure; 3) public services; 4) digitalization of organizations and businesses, which contribute to the digital revolution. The implementation and maintenance of digital solutions have highlighted the crucial role of an agile, flexible and resilient public sector. By increasing their capacity, countries have led the digital transformation, expanding international technology cooperation. In the case of Morocco, in 2017, the Agency for Digital Development (ADD) was created, thanks to which digital transformation and Morocco is increasingly entering the "digital channel", developing its strengths. In 2021, Morocco put into operation the most powerful supercomputer in Africa (African Supercomputing Centre), which provides high security, maximum availability, high flexibility and the optimal link for the efficient operation of the national digital ecosystem to ensure Morocco’s digital sovereignty and the development of digital services. The experience of Portugal also provides many valuable insights and lessons for digital reformers seeking to accelerate their digital transition and how important it is to institutionalise a politically empowered governance structure in the centre of government driving the reforms and unblocking resistance to change. The Strategy for the Digital Transformation of Public Administration 2021-2026 and the Action Plan for the Digital Transformation 2021-2023 envisioned a more digital Public Administration, encompassing digital strategic lines of action. The Interoperability platform of the public administration is now connected with the national e-delivery access point, which will allow the implementation of cross-border projects. The panel seeks to answer the following questions: what kind of initiatives can be identified in both countries that face similar challenges and are located in different realities? How can public sector organizations at the local or central level ensure the effective pursuit of digitalization and digital transformation?